LEARNING AND STUDY STRATEGIES INVENTORY (LASSI) AND ITS RELATIONSHIP WITH UNIVERSITY STUDENTS' ACADEMIC ACHIEVEMENT - Mahdokht Taheri; Ataollah Asadi Louyeh; Narges Hosseini (Informascope, 2017)
Lack of learning and study strategies (LASS) is one of the most important reasons for frustration and academic failure in student, so learning and study strategies resemble a tool applied in solving academic problems, assisting the students to develop the skills required in their academic course. Identifying and enhancing these strategies helps the person go through college education successfully depending on their own capabilities, discovering and strengthening them. So, the aim of the present study is the use of Learning and Study Strategies Inventory (LASSI) and its relationship with university students' academic achievement. The study results did not show remarkable relationship between the three main LASS and academic achievement (AA) among students of Guilan University of Medical Science and levels of LASS are very low among these students. Concerning the criticality of the students' AA, the academicians of this university are recommended to take some measures in order to decrease academic failure and improve it via boosting the students' knowledge and skill.